2014
DOI: 10.1530/eje-13-0523
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory adipokines contribute to insulin resistance in active acromegaly and respond differently to different treatment modalities

Abstract: Background: Active acromegaly is associated with insulin resistance, but it is uncertain whether inflammation in adipose tissue is a contributing factor. Aim: To test if GH/IGF1 promotes inflammation in adipocytes, and if this is relevant for systemic insulin resistance in acromegaly. Furthermore, to investigate the effect of treatment modalities (transsphenoidal surgery (TS), somatostatin analogs (SAs), and pegvisomant (PGV)) on glucose metabolism and inflammatory biomarkers in acromegaly. Methods: The in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 40 publications
0
17
1
1
Order By: Relevance
“…The effect of GH-reducing therapy on serum adiponectin levels has also been studied [21,22]. Olarescu et al measured adipokines in 37 patients with active acromegaly before and after treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of GH-reducing therapy on serum adiponectin levels has also been studied [21,22]. Olarescu et al measured adipokines in 37 patients with active acromegaly before and after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the transsphenoidal surgery (TS) group, adiponectin, vascular endothelial growth factor-A (VEGF-1), monocyte chemotactic protein 1 (MCP1), and thioredoxin (TRX) decreased significantly. In the somatostatin analogs (SA), group leptin increased, while in the pegvisomant (PGV) group HMWAD increased significantly [21]. Silha et al found increased, rather than decreased, adiponectin levels in a study involving 18 patients with acromegaly compared to BMI-and sex-matched controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful surgical and pharmacological treatments for acromegaly improve insulin resistance and the unfavorable lipid profile but increase fat mass [9,14,15,16,17,18]. In the general population, there is an association between the quantity of VAT and metabolic risk, but it is currently unknown whether a decreased fat mass, especially in visceral locations, has an influence on the metabolic risk profile in patients with acromegaly.…”
Section: Introductionmentioning
confidence: 99%
“…The white visceral adipose tissue produces different mediators, the adipokines, and a strong association between metabolic risk and fat distribution or adipokine levels has recently been documented [6]. The adipose dysfunction, resulting in higher lipolytic activity, changes the production and secretion of adipokines known to play a role in the pathogenesis of low-grade systemic inflammation and insulin resistance [7], leading to a cardiovascular disease and systemic metabolic complications [8,9]. In this view, the relation between GH and adipokine levels could explain the metabolic risk associated with acromegaly, although to date the data on adipokine levels in acromegaly are discordant.…”
Section: Introductionmentioning
confidence: 99%